2001
DOI: 10.1002/rcm.462
|View full text |Cite
|
Sign up to set email alerts
|

Comparative quantitative fatty acid analysis of triacylglycerols using matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry and gas chromatography

Abstract: Quantitative analyses of fatty acids from five triacylglycerol products, coconut oil, palm kernel oil, palm oil, lard and cocoa butter, were carried out using two analytical methods: matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOFMS) and gas chromatography (GC), in an effort to validate the application of MALDI-TOFMS in quantitative fatty acid analysis. For the GC analysis, transmethylated products were used, whereas, for the MALDI-TOF analysis, saponified products were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(7 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Indeed, for molecules lacking basic sites, such as sugars, cationization can be accomplished by the addition of alkali ions . This is also true when using the matrix F20TPP, which is usually mixed with sodium or potassium salts to ionize the analytes of interest. , We investigated the effect of lithium, sodium, potassium, rubidium, and cesium iodide on the detection limits of lopinavir and ritonavir. Iodide was chosen as counteranion, because the lower lattice energy of alkali iodides compared to other alkali halides results in more free gaseous alkali ions and, thus, higher signal abundances of the cationized analytes .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, for molecules lacking basic sites, such as sugars, cationization can be accomplished by the addition of alkali ions . This is also true when using the matrix F20TPP, which is usually mixed with sodium or potassium salts to ionize the analytes of interest. , We investigated the effect of lithium, sodium, potassium, rubidium, and cesium iodide on the detection limits of lopinavir and ritonavir. Iodide was chosen as counteranion, because the lower lattice energy of alkali iodides compared to other alkali halides results in more free gaseous alkali ions and, thus, higher signal abundances of the cationized analytes .…”
Section: Resultsmentioning
confidence: 99%
“…These abundant matrix-related peaks seriously hamper the qualitative and quantitative analysis of small molecules. One way to avoid such interference signals is to choose a matrix whose molecular weight is in excess of that of the analyte molecule. , Meso-tetrakis(pentafluorophenyl)porphyrin (F20TPP) is such a high molecular MALDI matrix (MW = 974.6 Da) and has successfully been used for the analysis of various small molecules, for example, poly(ethylene glycol)s, fatty acids, and sugars. …”
mentioning
confidence: 99%
“…Due to matrix interference, MALDI MS is infrequently used for the analysis of relatively small molecules. Nevertheless, under appropriate experimental conditions, MALDI-TOF MS enables robust and reliable analysis of unfractionated FAs and their derivatives, consistent with the GC determination, as well as the simultaneous detection of mono-, di-, and tri-acylglycerols 15 , 16 . The MALDI-TOF MS spectrum of Mann-S1 is shown in Supplementary Material (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…It has been reported that the antioxidant activity of VCO is higher than that of refined coconut oil, and its supplementation has beneficial effects on blood lipids by reducing the hepatic lipogenesis and increasing the formation of bile acids [14,15] . In addition, the coconut oil contains high amount of lauric acid (LA), also called n-dodecanoic acid, which is a medium-chain fatty acid that forms monolaurin in the human or animal body [16] . Previous studies have demonstrated many beneficial biological effects of LA [17] .…”
Section: Introductionmentioning
confidence: 99%